The Cataract National Dataset electronic multicentre audit of 55 567 operations: when should IOLMaster biometric measurements be rechecked? - Knox Cartwright, N E; Johnston, R L; Jaycock, P D; Tole, D M; Sparrow, J M (Eye (London), 2010)
Purpose Calculation of intraocular lens (IOL) power for implantation during cataract surgery depends on ocular biometric measurements. The aim of this study was to characterise the normal range of intra- and interindividual variation in axial length (AL) and corneal power ( K ) when IOLMaster measurements were possible and to derive recommendations as to which outlying measurements merit verification before acceptance. Methods The Medisoft electronic patient database contains prospectively collected data conforming to the United Kingdom (UK) Cataract National Dataset on 55 567 cataract operations. From this AL and K information on the 32 556 eyes (14 016 paired) of patients older than 25 years, without corneal pathology, history of intraocular surgery and who had all biometric measurements taken with the Zeiss IOLMaster (Carl Zeiss Meditec) were extracted. R 2.8.1 (R Foundation for Statistical Computing) was used for statistical analysis. Results Mean age was 76.4 years and 62.0% were female. Mean (95% confidence interval) values for AL, mean K and corneal astigmatism were 23.40 (21.27–26.59) mm, 43.90 (40.94–47.01) D and 1.04 (<2.50) D. Nearly all astigmatism was either with or against the rule. Differences between paired eyes were not statistically significant. 95% individuals had asymmetry of AL and mean K <0.70 mm and 0.92 D, respectively. Conclusions On the basis of approximation of the 95% CI above, it is suggested that AL, mean K and keratometric astigmatism measurements outside the ranges 21.30–26.60 mm, 41.00–47.00 D and >2.50 D, respectively, and intraindividual asymmetry of AL >0.70 mm or mean K >0.90 D should be verified before acceptance.